(untitled) - Moran, Michael J. (New York, 1992)
Contents: introductory concepts and definitions; Energy and the first law of thermodynamics; Properties of a pure, simple compressible substance; Control volume energy analysis...
Keywords: Thermodynamics,Nhiệt động lực học